Multiple endocrine neoplasia type 1 in children and adolescents: Clinical features and treatment outcomes - Shariq, O; Lines, K; English, K; Richards, D; Jafar-Mohammadi, B; Boon, H; Mihai, R; Richards, D; Thakker, R (Elsevier, 2021)
Background: Clinical manifestations and treatment outcomes in children and adolescents with multiple endocrine neoplasia type 1 are not well characterized.